The Philosophy of Greek Rationalism - Islamic Spirituality and Classical Islamic Education Theory: Al-Farabi and Ibnu Sina - Rosa Ramadhona; Ismail Sukardi; Mardiah As (The Future of Education Journal, 2024)
This study explores the interplay between Greek rationalism and Islamic spirituality in the context of classical Islamic education theories by Al-Farabi and Ibn Sina. Greek rationalism, represented by figures like Socrates, Plato, and Aristotle, emphasizes logic and reasoning, while Islamic spirituality integrates these principles with moral and spiritual values from Islamic teachings. Through a library research methodology, this study examines how these traditions have influenced the educational philosophies of Al-Farabi and Ibn Sina, focusing on their perspectives on educational objectives, teaching methods, and the integration of moral values. Al-Farabi’s concept of the “ideal society” highlights the role of education in shaping intellectually and ethically exemplary individuals, while Ibn Sina emphasizes an interdisciplinary and rational approach to learning, adapted to students' developmental stages. The findings demonstrate that integrating rationalism and spirituality can provide a holistic educational model that develops intellectual, emotional, and spiritual capacities. This approach is relevant for addressing modern educational challenges and fostering a balanced human development framework.